Effects of Soil Tillage, Management Practices, and Mulching Film Application on Soil Health and Peanut Yield in a Continuous Cropping System - Yang, Dongqing; Liu, Yan; Wang, Ying; Gao, Fang; Zhao, Jihao; Li, Ying; Li, Xiangdong (Frontiers in Microbiology, 2020)
Our objective was to optimize soil management practices to improve soil health to increase peanut (Arachis hypogaea L.) yield. We studied the effects of using rotary tillage with mulching film (RTMF) or without (RTNM), plow tillage with mulching film (PTMF) or without (PTNM), and green manure with mulching film (GMMF) or without (GMNM) over 3 years in Taiʹan, China. Results showed that, compared to RTNM treatment, GMNM and GMMF treatments significantly (P < 0.05) increased soil organic carbon, enzymatic activity, and the available nitrogen, phosphorus, and potassium content. The dominant bacterial phyla in the soil across all treatments were Proteobacteria, Acidobacteria, and Actinobacteria. Bacterial richness and diversity in the soil were significantly (P < 0.05) enhanced after GMMF and GMNM treatments compared with those after RTNM treatment. The linear discriminant analysis effect size analysis indicated that Chloroflexi abundance in the 0–10 and 10–20 cm soil layers changed significantly (P < 0.05) after RTMF and RTNM treatments, respectively, whereas that of Bacteroidetes changed significantly (P < 0.05) in the 0–10 layer after GMNM treatment. The abundance of the Xanthobacteraceae family of Proteobacteria in both soil layers changed significantly (P < 0.05) after GMNM and GMMF treatments. Redundancy analysis revealed that soil physical (soil bulk density and water content), chemical (soil organic carbon, available nitrogen, phosphorus, and potassium), and biological (soil enzymatic activity and nutrient content) characteristics affect the soil bacterial community. Changed soil quality indices may be favorable for leaf photo-assimilate accumulation. Compared with RTNM treatment, GMNM and GMMF treatments significantly increased photosynthesis rate in the peanut leaf and decreased intercellular carbon dioxide concentration. Our results showed that, compared to that after RTNM treatment, the average pod yield after GMMF and GMNM treatments increased by 27.85% and 21.26%, respectively, due to increases in the pods per plant and plant numbers. The highest yield of all treatments was obtained from the GMMF-treated plot, followed by that from the GMNM-treated plots. Thus, taking into consideration the residual pollution caused by plastic films, we propose GMNM as a suitable strategy to improve soil physicochemical and microbial properties and to increase the peanut pod yield.